ANALISIS HUKUM TERHADAP PENJATUHAN PIDANA DI BAWAH ANCAMAN MINIMUM KEPADA PELAKU TINDAK PIDANA KORUPSI - Arianus Harefa (Jurnal Education and Development, 2020)
Corruption in Indonesia has become widespread. Its development continues to increase from year to year, both in the number of cases that occur, the amount of state financial losses and in terms of the quality of criminal acts committed more systematically and have entered all aspects of public life. Corruption is an extraordinary crime, so extraordinary handling is also needed and extraordinary measures are also needed. In handling these crimes, adequate law enforcement is needed, namely judges in imposing penalties by giving the heaviest sanctions to the perpetrators. The maximum sentence imposed as a form of deterrent effect both to the perpetrators themselves and to others. Based on this, the purpose of this research is to know and analyze the basis of judges' judgment in dropping criminal decisions under the minimum threat to the perpetrators of criminal acts of corruption. This study uses a type of normative juridical research with an approach to the legislation in force. And the data used are secondary data, with data analysis is descriptive qualitative data analysis. Based on the results of the study showed that the basic consideration of judges in passing criminal decisions under the minimum threat to the perpetrators of corruption is that in proving corruption acts, judges are based on the theory of the negative verification system implied in Article 183 KUHAP (of the Criminal Procedure Code), which before giving a criminal verdict, the judge must consider the legal basis, and the non-juridical basis, and the judge considers the philosophical basis, while the judge in imposing a crime under the minimum threat to the perpetrators of criminal acts of corruption is based on desert theory or proportionality theory, namely penalties or penalties imposed by the judge considers the size of the state financial loss caused by the defendant with the facts that are revealed in court and other matters that are alleviating the actions of the accused during the trial process.